Students’ Perceptions of the Application of the Full Day School System in Senior High School Negeri 1 Dampal Utara - Ahdal Ahdal; I Nengah Kundera; Muhammad Jamhari (Equator Science Journal, 2024)
This study aims to describe the perceptions of SMA Negeri 1 North Dampal students towards the implementation of the Full Day School system. This type of research is descriptive research with a qualitative approach. The population in this study were all SMA Negeri 1 North Dampal students totaling 365 students consisting of 131 grade X students, 120 grade XI students, and 114 grade XII students. The number of samples in this study were 38 people. The sampling technique used Random Sampling. This research was conducted in April 2024. Data collection in this study used observation, questionnaires, interviews, and documentation techniques. The results showed that the majority of students have a positive perception of the implementation of the Full Day School system. This is evidenced by the percentage of good categories which reached 50% of the questionnaire results table and was supported by the development of IMTAK which reached a percentage of 100% with a very good category, increasing the creativity of students' interests and talents which reached a percentage of 92% with a very good category, and students felt the benefits of implementing the Full Day School system reaching a percentage of 78% with a good category. So it can be concluded that the perceptions of SMA Negeri 1 North Dampal students towards the implementation of the Full Day School system are categorized as good perceptions with positive respondents' responses.